2013
DOI: 10.3171/2013.3.jns13574
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Radiosurgery for parasagittal and parafalcine meningiomas

Abstract: Ding and colleagues at the University of Virginia review their results after Gamma Knife surgery for parasagittal and parafalcine (PSPF) meningiomas.1 This analysis details outcomes in 65 patients with 90 WHO Grade I tumors with an average imaging follow-up of almost 5 years. The tumor control rate was 85% at 3 years and 70% at 5 years, which is somewhat less than other long-term radiosurgery reports in patients with Grade I meningiomas. This may reflect the fact that cranial base tumors were not included, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Literature data focused on RS and SRT outcomes for parasagittal and parafalcine meningiomas are very limited 8,10,18,19. Five studies were found reporting the lesion outcomes,8,16,1921 in which only one single dose RS was employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data focused on RS and SRT outcomes for parasagittal and parafalcine meningiomas are very limited 8,10,18,19. Five studies were found reporting the lesion outcomes,8,16,1921 in which only one single dose RS was employed.…”
Section: Resultsmentioning
confidence: 99%
“…Addressing this issue could provide crucial information on the index of proliferation and neurobiological characteristics associated with the molecular pathways that regulate the apoptotic response of tissue, cellular, and genetic post-irradiation damage 52. With regard to the management of these tumors, some authors suggest be planned RS within a few months if a larger lesion with mass effect has been resected 18. Due to the high recurrence rate reported, even when an apparently total resection is obtained, a multidisciplinary approach is mandatory for parafalcine and parasagittal meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Radiosurgery has also a risk of symptomatic imaging-demonstrated changes, which are frequently transient. 36 The risk of such adverse radiation events (AREs) after SRS is mostly related to symptomatic edema or damage to the cranial nerves. In a recent meta-analysis, 43 which included 4229 patients, the overall relative frequency of AREs was 8.1% (range 5.2%–11.5%).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Combined Approaches With Planned Subtotal Resection Followed by Radiosurgery During the past years, combined approaches with postoperative adjuvant radiosurgery on the postoperative residual tumors have been proposed, 33 aiming at conserving neurological function. [34][35][36] Such approaches depend mainly on the residual tumor volume to safely perform SRS as an adjuvant therapy. 37 Long-term tumor control after SRS also depends on histology, being as high as 93%-95% for WHO grade I, 50%-60% for WHO grade II, and decreasing to 10%-17% for WHO grade III.…”
Section: Meningiomas Involving Major Dural Sinusesmentioning
confidence: 99%